Land use and land cover changes in Kullu valley of Himachal Pradesh - VAIDYA, PRATIMA; BHARDWAJ, SATISH KUMAR; SOOD, SAHIL (The Indian Journal of Agricultural Sciences, 2018)
Land use changes are the land conversions from one type to another that alter the earth surface to satisfy mankind's immediate demand. Land use change detection using satellite imageries has emerged important mean to gather information on regional scale changes. Present study envisaged the spatio-temporal land use land cover changes of Kullu valley of Himachal Pradesh using LANDSAT imageries of 1989 and 2016. The results were verified through the secondary data as well as primary data collected by detailed survey of the Kullu valley (Kullu and Naggar blocks) and drivers for such changes were also identified. The studies were carried out for major land use type, viz. agriculture, orchard, forest and built up in the valley over a period of 27 years. Supervised classification was done using Maximum Likelihood Classification Algorithm through ERDAS Imagine 14 software. The results indicated that during last 27 years, the built up area has increased to the extent of 90.81% followed by orchards (12.39%) and forest (6.26%), whereas area under agriculture was decreased by 56.88%. The primary data revealed that farmers are abandoning the wheat, paddy, maize and barley crops and are pursuing cultivation of vegetable and fruit crops. Increased economic returns and climate change emerged as the probable drivers for the changes in the valley.